Capital and Labor Reallocation within Firms - GIROUD, XAVIER; MUELLER, HOLGER M. (Journal of Finance, 2015)
ABSTRACT We document how a positive shock to investment opportunities at one plant (“treated plant”) spills over to other plants within the same firm, but only if the firm is financially constrained. To provide the treated plant with resources, the firm's headquarters withdraws capital and labor from other plants, especially plants that are relatively less productive, not part of the firm's core industries, and located far away from headquarters. As a result of the resource reallocation, aggregate firm‐wide productivity increases. We do not find evidence of capital or labor spillovers among plants of financially unconstrained firms.